Metal-Catalyzed C–H Bond Oxidation in the Total Synthesis of Natural and Unnatural Products - Santana, Victor C. S.; Fernandes, Milena C. V.; Cappuccelli, Isadora; Richieri, Ana Carolina G.; de Lucca Jr, Emilio C. (Synthesis, 2022)
C–H bond oxidation is a powerful means for oxygen incorporation in organic molecules. Its use results in fast structural diversification and in a new way of thinking about retrosynthetic disconnections. In this review, we present the application of five metal-catalyzed methodologies for C(sp3)–H oxidation in the total synthesis of natural and unnatural products, covering the period of 2004–2022.1 Introduction2 Copper-Mediated Hydroxylation of Methylenes β to Imines3 Palladium Acetoxylation of Methyl Groups β to Oximes4 Palladium-Mediated Allylic C–H Bond Oxidation of Terminal Olefins5 Iron- and Manganese-Mediated Aliphatic Oxidation6 Miscellaneous7 Conclusion
Keywords: C–H bond oxidation; catalysis; total synthesis; natural products; transition metals